69. PERMANENT INTRACAVITARY Cs131 BRACHYTHERAPY FOR PREVIOUSLY-IRRADIATED RECURRENT BRAIN METASTASES: INITIAL CLINICAL AND RADIATION SAFETY EXPERIENCE - Moss, Nelson S (Neurooncol Adv, 2020)
OBJECTIVE: Recurrence of previously-irradiated brain metastases (BrM) presents a significant challenge. We describe our initial experience using salvage resection with Cs131 brachytherapy in previously-irradiated BrM. METHODS: Between September 2019 and April 2020, 9 patients with recurrent BrM underwent maximally-safe metastatectomy. Following pathological confirmation of viable recurrence, cavities were implanted with permanent Cs131 brachytherapy (GammaTile, GT Medical Technologies). Prescribed dose was 60Gy at 5mm from the cavity. Postimplant dosimetry (V100) was calculated on postoperative day 1 fused CT/MRI. Intraoperative team exposure was recorded using intraoperative ring dosimetry, and patient dose-rates measured postoperatively informed patient, family and medical-staff exposure modeling. RESULTS: Nine patients (55% female, median age 54) underwent 10 implantations (6 supratentorial, 4 infratentorial). Median preoperative maximum diameter was 3.5cm (2.3–6.3) and histologies included breast, gastrointestinal, lung, kidney and oral cavity squamous cell carcinomas. Five had undergone prior resection or laser ablation. All lesions received >/=1 prior course of stereotactic irradiation a median of 10.1 months (3.7–15.9) earlier. Eight lesions were gross-totally resected. Median number of implanted Cs131 seeds was 16 (12–28) with median seed strength of 61.8U (42.4–98.0). Median postoperative cavity size was well-correlated with the number of implanted seeds (Pearson R=0.75, p=0.03). Median V100 dose coverage of the cavities and uniform 5mm expansion of the cavities were 99% (79–100%) and 79% (51–95%), respectively. Median measured exposure rates were 90mR/hr (28–152) on contact, 9.15mR/hr (2.7–13.9) at 30cm and 1.4mR/hr (0.6–2.3) at 1 meter from the patient. Mean ring dose was 6.83mrem (0–18) for the radiation oncologist and 9.17mrem (0–15) for the neurosurgeon. Modeled lifetime family-member and visitor exposure was 116mrem (52-193mrem), and healthcare worker exposure was 39mrem (17-64mrem), all well below regulatory limits. There were no immediate wound complications or unanticipated neurologic injuries. CONCLUSION: In our early experience, salvage interstitial Cs131 implantation was safely employed for recurrent brain metastases.